Evaluation Of Crossing Vessel Operation Patterns On The Kariangau-Penajaj Port Kariangau East Kalimantan Province - Argo, Junian Budi; Amanda, Monica; Ulya, Febriyanti Himmatul; Puspitasari, Novrianti; Dewi Apriani , Dahlia; Wulandari, Devita Eka (IWJ : Inland Waterways Journal, 2023)
Kariangau Ferry Port is a port in Balikpapan City which serves the Kariangau-Penajam route with a total of 12 ships per day. Ship operations on this route are not balanced with minimum service standards for ship operations and the ideal number of trips so that when the ship sails it does not carry maximum passengers or vehicles. This research aims to increase the efficiency of ship use based on the current ideal number of ships and trips and minimum service standards for ship operations. The method used in this research is analysis load factor, analysis of minimum service standards for ship operations, analysis of ship needs, and scheduling analysis. Based on the results of the calculation analysis load factorobtained on averageload factorfor passengers it is currently 1% and for vehicles it is currently 57%. The change in ship operating patterns on the Kariangau-Penajam route now from existing conditions, which was obtained through the results of analysis of the calculation of the need for the number of ships and analysis of optimal ship schedules, has caused differences between the current ship operating patterns and the planned operation patterns resulting from the calculations. The operating pattern of this plan is calculated based on the number of trips and the number of ships according to the needs of service users so that ships on this route can carry maximum passengers and vehicles.load factorideal 65%.